Development of E-Assessment Monitoring of Child Growth and Development (SI INTAN) in Kindergarten Abdi Pertiwi - Rivo Panji Yudha; Yusmarini, Intan (Kirana Publisher (KNPub), 2024)
This study aims to determine the needs analysis of E-Assessment (Si Intan) monitoring child growth and development, to test the feasibility of E-Assessment (Si Intan) monitoring child growth and development, and to test the practicality of E-Assessment (Si Intan) monitoring child growth and development in Abdi Pertiwi Kindergarten. This research is a type of research and development (Research and Development). The research and development model of education (Research and Development) carried out adopts the 4-D development model (Four-D) with research stages, namely, define, design, develop, and dissemination. It's just that researchers limit this research to the development stage, namely product practicality testing, not to the dissemination stage due to limited time and researcher costs. The results of the needs analysis show that teachers and parents need new assessment products on children's growth and development whose results of identifying needs Regarding Media New assessments that answer yes are in the qualifications are needed so that they become the basis for researchers in developing this e-assessment (Si Intan). The results of the validation of this e-assessment product (Si Intan) are valid and reliable, the results of this validity consist of trials on 2 validators, namely media expert validators on the e-assessment product (Si Intan) who get good qualification validity test results. As well as the results of the validity of the assessment expert on this e-assessment product (Si Intan) get good qualification results. The results of the reliability union show an average agreement between raters of 0.125 while for raters the consistency is 0.932 which means it has high stability.